Pengaruh Keterlibatan Pegawai dan Pengembangan Karir Terhadap Loyalitas Pegawai Badan Kesatuan Bangsa dan Politik Kutai Timur - Ibrahim Ibrahim; Djoko Setyadi; Purwinahyu Purwinahyu (INDO PUBLISHING, 2026)
This study aims to analyze the influence of employee engagement and career development on employee loyalty at the National Unity and Politics Agency (Kesbangpol) of East Kutai Regency. The research background is grounded in the dynamics of employment status transitions from Regional Contract Workers (TK2D) to Government Employees with Work Agreements (P3K), which significantly affected career expectations and work engagement levels in local government institutions. A quantitative approach with descriptive and inferential statistical design was employed. The population and sample consisted of all 61 employees of Kesbangpol East Kutai using total sampling (census) technique. Data were collected through a Likert scale questionnaire (1–5) and analyzed using multiple linear regression, partial t-test, and simultaneous F-test, preceded by classical assumption tests including normality, multicollinearity, autocorrelation, and heteroscedasticity. Results showed: (1) employee engagement had a positive and significant effect on employee loyalty (t = 2.026; sig. = 0.047); (2) career development had a positive and significant effect on loyalty (t = 4.435; sig. = 0.000); (3) simultaneously, both variables significantly affected employee loyalty (F = 26.958; sig. = 0.000) with a contribution of 48.2% (R² = 0.482). These findings confirm that strengthening employee engagement through empowerment and participatory work, alongside developing a transparent and equitable career system, are key strategies for building employee loyalty in local government institutions.